Martha’s Dialogue with Jesus (John 11,21-27) in Light of the Psalms of Lament - Richard Francis D’Souza OCD (Warszawskie Studia Teologiczne)
First part of this paper is a study of the structure of Martha’s dialogue with Jesus (John 11,21-27) in comparison with the lament psalm (Ps 13) as proposed by G. O’Day. While the first part of the dialogue corresponds to the plea section of a lament psalm with the constituent elements of address, complaint, petition, and motivation (Jn 11,21-22), the second part mirrors the praise section of the psalm which consist of words of assurance and divine praise (Jn 11,23-27). The second part of the paper is a theological interpretation of the profound dialogue between Jesus and Martha. While the dialogue explains in advance the significance of the sign of raising Lazarus from the dead, it also highlights the progressive faith journey of Martha from the initial lament to the highest confession of faith in Jesus as the Messiah and the Son of God.